Analysis Of Regional Acceptance Potentials From The Tourism Sector In West Kotawaringin, East Kotawaringin, And Palangka Raya City - DAHLIA DAHLIA; HARIN TIAWON (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2019)
This study aims to analyze and determine the potential revenue of the tourism sector on Regional Original Income in three regions, namely West Kotawaringin Regency, East Kotawaringin Regency, and Palangka Raya City. The data used is qualitative data and is also supported by quantitative data, the method used in this research is descriptive qualitative. Data analysis uses the contribution of tourism income to Regional Original Income, namely using an analysis of the contribution of PAD based on the classification of contribution criteria. The results of this study indicate that the different tourist characteristics between the three regencies/cities have their own tourist attractions. But the number of tourists visiting only come directly to the tourist attraction, so that previously the tourism industry was a source of income for the private sector and the region through restaurant taxes or hotel taxes, now the source of income from the tourism industry is less contributing to Regional Original Income